(untitled) (Baghdad Science Journal, 2011)
In this research (100* 40* 4 cm) solar cell panel was used in Baghdad at autumn season (2010), to get best solar cell panel angles experimentally, and then a mirror (40*50 cm) is use to concentrate incident sunlight intensity on a panel. At first case we get (Tilt angle ?P =60°and Surface Azimuth angle ?P =36°E) is the best angles and other case, we add a mirror at angle = 120° at bottom of panel, then we get output power (27.48watt) is bigger than without using a mirror (25.16watt). We can benefit from these cases in variety applications.